2019
DOI: 10.1007/s13202-019-0646-5
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics study of yield power law drilling fluid flow through smooth-walled fractures

Abstract: Presence of natural fractures in sub-surface makes an oil well drilling operation very challenging. As one of the major functions of drilling mud is to maintain bottomhole pressure inside a wellbore to avoid any invasion of unwanted high-pressure influx (oil/gas/water), drilling a well through these fractures can cause severe mud loss into the formation and subsequent danger of compromising the wellbore pressure integrity. The aim of this paper is to carry out a Computational Fluid Dynamics (CFD) study of dril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Tang et al 14 conducted computational simulations of spiral laminar power-law flow in the partially blocked annulus, and the Fluent is used for the analysis. Ahammad et al 15 studied the computational fluid dynamics of power-law fluid flow through smooth-walled fractures based on CFD software ANSYS Fluent.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al 14 conducted computational simulations of spiral laminar power-law flow in the partially blocked annulus, and the Fluent is used for the analysis. Ahammad et al 15 studied the computational fluid dynamics of power-law fluid flow through smooth-walled fractures based on CFD software ANSYS Fluent.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, analyzing steam CHT of PCCS in the presence of NCG was essential. CFD and related simulation tools were widely used in fluid flow, heat transfer, and biomaterial applications (Khan et al, 2017;Ahammad et al, 2019;Saha et al, 2020;Hasan et al, 2021). Additionally, CFD and related simulation tools were commonly used in various nuclear reactor applications (Mahaffy et al, 2007;Shamim et al, 2016;Sharma et al, 2019;Ahmed, 2021aAhmed, , 2021bBhowmik and Suh, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of numerical simulation processes has provided a convenient and effective means to study both temperature and flow fields [18]. The computational fluid dynamics (CFD) technique was implemented to analyze the flow behavior of oil in wells and caves, because CFD makes it possible to numerically solve flow, mass, and energy balances [19]. This study found that in the previous related research reports, the adopted transient wellbore simulations had mainly focused on the mud circulation during the drilling and subsequent shut-in stages.…”
Section: Introductionmentioning
confidence: 99%